Traços funcionais de espécies arbóreas de cerrado sensu stricto e sua importância para a manutenção de comunidades nativas - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Functional traits are morphofisiolocical characteristics of each species capable of significantly influence the ecological processes in their natural environment and can be used to form functional groups. Functional groups are species with similar traits and functions on communities. This study aimed to describe the functional traits of tree species of cerrado sensu stricto and we tried to answer if 1) is possible to group the species into functional groups, 2) which traits varied more and which best explained the survival of these species and 3) the groups found for cerrado sensu stricto are similar with forest functional groups. Leaf function, specific leaf area, dry mass, leaf water quantity and leaf water percentage) and architecture (total height, diameter, height of the 1st branch, crown volume area, biomass and wood density) of 33 tree species of cerrado sensu stricto with a circumference greater than or equal to 15 cm at 0,30 m height were measured. The analysis of variance between the traits and the Scott-Knott test was performed, a principal components analysis was performed a dendrogram of similarity with the normalized data of each trait was calculated by Ward's and UPGMA grouping methodrictu. Group 1 had the highest density of wood, dry mass and leaf area, with high values of volume and biomass. The most species of G1 had compound leaves with low specific leaf area and the highest leaf area and mass dry. Group 2 were formed by small species, with low crown volume and biomass, however with the highest specific leaf area and leaf percentage of water. The group 3 was formed by species with the lowest biomass and canopy volume, and also presented low values of wood density, foliar area and dry mass. The group 4 had the highest values of canopy volume, biomass and bark, constituting the group of species with the largest size, however, presented low values of specific leaf area and leaf percentage of water. We demonstrate that it is possible to delimit species of cerrado sensu stricto in, at least, 4 different functional groups, and the traits that best explained the presence of these were specific leaf area, leaf area, dry mass, leaf water percentage, topography, crown volume, biomass and wood density.
Keywords: Resiliência; grupos funcionais; fogo; sazonalidade; Resilience; functional groups; fire; seasonality; CIENCIAS AGRARIAS